2000
DOI: 10.7326/0003-4819-132-3-200002010-00002
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Manual Physical Therapy and Exercise in Osteoarthritis of the Knee

Abstract: A combination of manual physical therapy and supervised exercise yields functional benefits for patients with osteoarthritis of the knee and may delay or prevent the need for surgical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
435
1
30

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 544 publications
(487 citation statements)
references
References 23 publications
13
435
1
30
Order By: Relevance
“…The small number of participants (n=204) and inter-study heterogeneity may have influenced this finding. Long-term (>6 months) follow-ups of exercise-based RCTs have found that post-treatment improvements in pain and function were not maintained [13][14][15] , but it is unclear at what point benefits dissipate following treatment and long-term follow-up. There is therefore a need to identify the medium-term effects of physiotherapy for hip OA.…”
Section: Authorsmentioning
confidence: 99%
“…The small number of participants (n=204) and inter-study heterogeneity may have influenced this finding. Long-term (>6 months) follow-ups of exercise-based RCTs have found that post-treatment improvements in pain and function were not maintained [13][14][15] , but it is unclear at what point benefits dissipate following treatment and long-term follow-up. There is therefore a need to identify the medium-term effects of physiotherapy for hip OA.…”
Section: Authorsmentioning
confidence: 99%
“…The patient's percentage improvements on her KOOS subscale scores were higher than scores attained by patients undergoing manual therapy and exercise treatments reported in the literature. 8 Although this patient experienced setbacks in her pain level and functionality from discharge to the 16-week follow-up, she maintained and even exceeded many other discharge scores; also, both of these KOOS subsection scores remained higher than the scores reported at baseline ( Table 2). The patient continued unrestricted softball activities after discharge, and follow-up outcomes were assessed within a few days of beginning preseason training.…”
Section: Discussionmentioning
confidence: 72%
“…Similar studies examining the effects of manual therapy and exercise on patients with OA of the knee reported only 20% to 40% relief of symptoms after 2 to 3 clinical treatments. 8 The patient's use of pharmacologic drugs was also not effective in significantly reducing pain over an extended period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical therapy, generally applied in the clinical setting directed by a therapist, is effective in reducing pain, stiffness, and disability and in increasing functionality among patients with knee OA [8][9][10][11][12][13][14]. However, Fisher and colleagues found that only 2 percent of 500 patients who had knee OA had received any type of exercise therapy [13].…”
Section: Introductionmentioning
confidence: 99%